Consumers' awareness and practices towards 'exclusion clause' and its position under Malaysian law - Abu Bakar, Elistina; Amin, Naemah (Malaysian Consumer and Family Economics Association, 2016)
The aim of this paper is to explore the adequacy of contract law, common law and the Consumer Protection Act 1999 (CPA) as the tools of consumer protection in dealing with exclusion clauses. The underlying philosophy is that consumers are free to enter into contracts and therefore must take care of their own interests. This principle, which is based on the assumption of equal bargaining power between parties, though, is not appropriate when consumers are involved. This is because in most consumer transactions, the natural tendency is that the consumers have no option except to abide by the contractual terms determined by the suppliers. The content analysis is carried out in order to analyse Malaysian law which include the analysis on the Contract Act 1950, the common law as well as the Consumer Protection Act 1999. A survey using questionnaires was carried out among 400 consumers in Klang Valley to explore their awareness and practices towards exclusion clauses. The analysis of the laws demonstrates that the law of contract, common law and the CPA are inadequate in giving comprehensive protection to consumers on the issue of exclusion clauses. In addition, the results of the survey show that only 41.8% of the respondents aware of the existence of such clauses in their dealing with the suppliers and 50.8 % of the respondents responded that they did not understand the implication of such clause. In total, 54.3% of them stated that they would still sign the document even though they were already aware of the exclusion clauses or any other unfair contractual terms. Thus, it is submitted that there are two solutions to this problem. The first one is to educate the consumers so that they are more aware about exclusion clauses and the second one is for the Parliament to take steps to legislate specific legislation dealing with exclusion clauses especially in consumer transactions.